Dual judicial system in a multi-religious and multi-racial country : with special reference to Malaysia - Al-Sabri Haji Ahmad Kabri (Ahmad Ibrahim Kulliyah of Laws,International Islamic University Malaysia, 2021)
The dual judicial system in Malaysia is a reality in theory but in practice it comes with some challenges and unforeseen obstacles. The predicament of one spouse's conversion/reversion into Islam and in those instances to which jurisdiction parties are subjected to is one of an example of the challenges. The right of audience before the respective courts when parties are of different faiths is the other obstacle. The courts in the country are trying its level best to avoid being put in the state of dilemma and uncertainty as it may occur in the implementation of the dual judicial system in the country. This research explores and critically analyses the challenges faced by the implementation of the dual judicial system in Malaysia by glancing back at the history of the emergence of these laws, analysing the real present day cases in courts on these issues and dissecting the ratio decidendi of the judgements, isolating the problems faced and comparing with the real treatment accorded by the honourable courts respectively before proposing solutions. This research also critically analyses the justification of using the doctrine of “basic structure” in interpreting the Federal Constitution. The research seems to find that there might be more unforeseen challenges to emerge in future if the issues and challenges are not addressed in the right manner. This study is important to ensure that the frictions created in the implementations of dual judicial system in Malaysia are minimised for its smooth sailing in the future. In addition, this study is significant to ensure Civil Courts and the Syariah Courts are to co-exist as a parallel judicial system in Malaysia in line with the wishes of the majority of the population of this beloved multi-racial and multi-religious country.